AIDs-related kaposi's sarcoma: Manifestations and management strategies with haart and adjuvant therapies - Charles AO; Umanah IN (Ibom Medical Journal, 2014)
AIDS-related Kaposi sarcoma varies widely from a few mucocutaneous lesions to more florid ones with life threatening visceral involvement. Highly active antiretroviral therapy (HAART) has radically improved the outcome of this disease, and is pivotal to any treatment of the tumour. Late disease will require adjuvant chemotherapy for some duration to induce remission. Less expensive chemotherapy regimens may be needed in sub Saharan Africa heavily burdened with the disease and poverty. Various biologic agents are undergoing clinical trials at different stages and may prove useful in controlling the disease when combined with HAART and chemotherapy.